The novel desmopressin analogue [V4Q5]dDAVP inhibits angiogenesis, tumour growth and metastases in vasopressin type 2 receptor-expressing breast cancer models - Garona, Juan (2015)
Desmopressin (dDAVP) is a safe haemostatic agent with previously reported antitumour activity. It acts as a selective agonist for the V2 vasopressin membrane receptor (V2r) present on tumour cells and microvasculature. The purpose of this study was to evaluate the novel peptide derivative [V4Q5]dDAVP in V2r-expressing preclinical mouse models of breast cancer. We assessed antitumour effects of [V4Q5]dDAVP using human MCF-7 and MDA‑MB‑231 breast carcinoma cells, as well as the highly metastatic mouse F3II cell line. Effect on in vitro cancer cell growth was evaluated by cell proliferation and clonogenic assays. Cell cycle distribution was analysed by flow cytometry. In order to study the effect of intravenously administered [V4Q5]dDAVP on tumour growth and angiogenesis, breast cancer xenografts were generated in athymic mice. F3II cells were injected into syngeneic mice to evaluate the effect of [V4Q5]dDAVP on spontaneous and experimental metastatic spread. In vitro cytostatic effects of [V4Q5]dDAVP against breast cancer cells were greater than those of dDAVP, and associated with V2r-activated signal transduction and partial cell cycle arrest. In MDA‑MB‑231 xenografts, [V4Q5]dDAVP (0.3 µg/kg, thrice a week) reduced tumour growth and angiogenesis. Treatment of F3II mammary tumour-bearing immunocompetent mice resulted in complete inhibition of metastatic progression. [V4Q5]dDAVP also displayed greater antimetastatic efficacy than dDAVP on experimental lung colonisation by F3II cells. The novel analogue was well tolerated in preliminary acute toxicology studies, at doses ≥300-fold above that required for anti-angiogenic/antimetastatic effects. Our data establish the preclinical activity of [V4Q5]dDAVP in aggressive breast cancer, providing the rationale for further clinical trials.